Upper extremity angular kinematics of the one-handed backhand drive in tennis players with and without tennis elbow - Knudson, D.; Blackwell, J. (International Journal of Sports Medicine, 1997)
Wrist and elbow angular kinematics and racket acceleration at impact were measured in the tennis one-handed back-hand drive for three groups of players: Professionals with no history of tennis elbow (PRO), intermediates with no history of tennis elbow (- TE), and intermediates with a history of tennis elbow (+ TE). Electrogoniometer, strain gauge, and accelerometer signals were sampled for thirty strokes at 1000 Hz. The first ten strokes with central impacts were analyzed. Angular kinematics and racket acceleration at impact were analyzed with planned comparisons ANOVA. A significant (p < 0.05) difference in mean wrist angular velocity after impact was observed between the PRO group (-4.04 rad/s of extension) and the + TE group (0.42 rad/s of flexion). No significant differences were observed in impact acceleration or elbow angular kinematics. Eccentric wrist extensor muscular actions through impact may be important area of study for one-handed backhands and TE.